2009
DOI: 10.1111/j.1476-5381.2009.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the CB1 receptor antagonists rimonabant and AM251 on the firing rate of dorsal raphe nucleus neurons in rat brain slices

Abstract: Background and purpose:Previous studies have suggested a regulation of 5-hydroxytryptamine (5-HT) neurons by the endocannabinoid system. The aim of our work was to examine the effect of two CB1 receptor antagonists, SR141716A (rimonabant, Sanofi-Synthélabo Recherche, Montpellier, France) and N-(piperidin-1-yl)-5-(4-iodophenyl)-1-(2,4-dichlorophenyl)-4-methyl-1H-pyrazole-3-carboxamide (AM251, Tocris Cookson, Bristol, UK), on the firing rate of dorsal raphe nucleus (DRN) neurons. Experimental approach: Single-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 35 publications
1
28
0
2
Order By: Relevance
“…In vitro studies provide a more direct role for eCB regulation of the DR-5-HT system. Several studies have shown that CB1r stimulation and administration of WIN 55,212-2 decrease glutamatergic signaling in DR-5-HT neurons [44, 45]; however, other findings indicate that eCB tone regulates DR-5-HT signaling by modulating GABAergic inputs to serotonergic neurons [46]. Neuroanatomical studies examining the synaptic relationship of CB1r with GABAergic and glutamatergic neurons are needed to better define sites of action of eCBs in the modulation of DR-5-HT signaling [46].…”
Section: The Endocannabinoid System and Monoaminesmentioning
confidence: 99%
“…In vitro studies provide a more direct role for eCB regulation of the DR-5-HT system. Several studies have shown that CB1r stimulation and administration of WIN 55,212-2 decrease glutamatergic signaling in DR-5-HT neurons [44, 45]; however, other findings indicate that eCB tone regulates DR-5-HT signaling by modulating GABAergic inputs to serotonergic neurons [46]. Neuroanatomical studies examining the synaptic relationship of CB1r with GABAergic and glutamatergic neurons are needed to better define sites of action of eCBs in the modulation of DR-5-HT signaling [46].…”
Section: The Endocannabinoid System and Monoaminesmentioning
confidence: 99%
“…The outcome of these studies also suggests that CB1 receptors are most likely located on glutamatergic terminals impinging on DR 5-HT neurons. In addition to the inhibition of glutamate release, a recent in vitro extracellular recording study reports that eCB tone in the DR can regulate the firing activity of 5-HT neurons by regulating GABAergic transmission (Mendiguren and Pineda, 2009). However, the detailed cellular mechanism of such regulation remains to be determined.…”
Section: Modulation Of the Excitability Of Dr 5-ht Neurons By Ecb mentioning
confidence: 99%
“…This result suggests that local application of 5F-ADB had no effect on serotonergic systems via either CB 1 receptors or serotonin receptors. Recent evidence shows that CB 1 receptor antagonists decreased serotonergic firing rates (Mendiguren and Pineda, 2009), suggesting that endocannabinoid levels are high even in acute brain slices. Therefore, we tested the effect of the CB 1 receptor antagonist AM251 (1 μM) on serotonergic firing rates.…”
Section: F-adb Did Not Affect Spontaneous Activity Of Midbrain Serotmentioning
confidence: 99%